PENGEMBANGAN ALAT BLOK PERMAINAN BOLA VOLI - Aprili, Isnani Sara; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to develop new innovations in the form of volleyball block tools that can help optimize the volleyball block training process and help optimize the results of volleyball smash exercises. This research is a research and development. This research uses the development method of ADDIE with several steps, namely: analysis, design, development, implementation and evaluation. The test subjects in this study were Pontianak City Rajawali club with 26 athletes in total as samples, 14 female athletes and 12 male athletes. The results of the Volleyball Game Block Tool research are categorized as